Anabolic-androgenic steroids for patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis - Liu, Yahui; Huang, Chunrong; Du, Juan; Lan, Gelei; Du, Xueqing; Sun, Yidan; Shi, Guochao (Frontiers in Medicine, 2022)
Background: Testosterone deficiency is common in chronic obstructive pulmonary disease (COPD) patients. There has been a growing interest in the potential use of anabolic-androgenic steroids (AASs) in patients with COPD recently. However, whether AASs could improve their clinical outcomes remains unknown. Methods: In order to explore the efficacy of AASs in patients with COPD, systematic search of MEDLINE, Embase, the Cochrane Library and ClinicalTrials.gov for randomized controlled trials (RCTs) of AASs for COPD published before March 17, 2022 was performed. Results: Data were extracted from 8 articles involving 520 participants. The median number of participants per study was 39.5 and the mean follow up was 14.2 weeks. As compared to the control group, AASs therapy could significantly improve body weight (weighted mean difference (WMD), 1.38kg; 95% CI, 0.79 to 1.97kg), fat-free mass (WMD, 1.56kg; 95% CI, 0.94 to 2.18kg) and peak workload (WMD, 6.89W; 95% CI, 3.97 to 9.81W) of COPD patients, but no improvements in spirometry indicators and six-minute walking distances (WMD, 16.88m; 95%, -3.27 to 37.04m). Based on the available research data, it is uncertain whether AASs treatment could improve the quality of life of COPD patients. Conclusions: Limited published evidence indicates that AASs therapy provides clinical benefits in patients with COPD. However, longer and larger studies are needed to better clarify the efficacy of AASs and draw final conclusions.